国有企业转制后存在的问题及对策初探 = Ownership reform in China's state owned enterprises : issues and options - 胡连鼎 Hu, Lianding (2008)
This paper focuses on the behavior of post-reform enterprises. A survey of 17 enterprises in Qinghuangdao City is conducted to gather information in relation to changes that have been brought about the ownership reform.